Development of Psychosocial Work Environment Model for the Petrochemical Industry Workers of Malaysia - JAVAID, MUHAMMAD UMAIR (2018)
The theme of the eleventh Malaysian plan (2016-2020) targeting vision 2020 is "anchoring growth on people" which visualizes Malaysia as a fully developed country along with economic, political, spiritual, cultural and psychological dimensions. This shows that the psychological health and wellbeing of the workers are central to the prosperous future of the Malaysian industry.